Effect of Sugar Palm Fiber Surface on Interfacial Bonding with Natural Sago Matrix - H. Mardin; I. N. G. Wardana; Pratikto; Wahyono Suprapto; Kusno Kamil (Advances in Materials Science and Engineering)
Palm fibers were immersed in sea water for 1, 2, 3, and 4 weeks prior to application as reinforcement of green biocomposite. Instead of common resin matrix, natural sago starch was applied as the matrix compound. The immersion treatments had significantly affected fibers surface morphology and interfacial bonds of fiber and the matrix as observed through Scanning Electron Microscopy (SEM). The quality of interfacial bonds became higher by additional duration of the sea water immersion. The best interlocking surfaces of fibers and matrix appeared in the composite with 4-week immersed fibers, indicated by disappearance of gaps between fiber and matrix. The morphology of fibers surface interlocking process was clearly seen during the duration of immersion.